2020
DOI: 10.3390/ijerph17072547
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Working Conditions and Well-Being of Migrant Workers in Spain

Abstract: This study examines the relationship beween employment and psychosocial working conditions and well-being of native and migrant workers in the working population of Spain. Data from the 7th Spanish Survey of Working Conditions was used to conduct a confirmatory factor analysis (n = 8508) to identify the main latent variables that influenced well-being. Using structural equation modeling and multivariate analysis, we found different patterns and perceptions of well-being and working conditions in these two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Few data are available on the health status of migrant workers in Europe, but previous studies in Nepal, Tanzania and Ethiopia have documented a low prevalence of HIV in migrant farm workers, low condom use, high risk of risky sex and high prevalence of malnutrition, and reinforce the need for screening for diseases related to a poor quality of work and life, which is strongly correlated with tuberculosis and non-communicable diseases, such as hypertension and diabetes, and overwork illnesses, such as rickets, asthenia, muscle/fatigue pain and mental health illnesses [ 11 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few data are available on the health status of migrant workers in Europe, but previous studies in Nepal, Tanzania and Ethiopia have documented a low prevalence of HIV in migrant farm workers, low condom use, high risk of risky sex and high prevalence of malnutrition, and reinforce the need for screening for diseases related to a poor quality of work and life, which is strongly correlated with tuberculosis and non-communicable diseases, such as hypertension and diabetes, and overwork illnesses, such as rickets, asthenia, muscle/fatigue pain and mental health illnesses [ 11 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Migrant workers typically have poorer social networks limiting opportunities to find work (Salvatore et al 2013 ). Migrant workers are more likely to work in unregulated sections of the labour market and are consequently exposed to social segregation and are vulnerable to exploitation and abuse (Alberti et al 2013 ; Bretones et al 2020 ; Thornley et al 2010 ).…”
Section: Characteristics Of International Migrants’ Workmentioning
confidence: 99%
“…Recent research has highlighted the mental health and social well-being problems of migrant workers and shows that migrant workers are more likely to suffer from psychosocial problems and mental disorders than the native workers (Bretones et al 2020 ; Daly et al 2019 ; Liu et al 2020 ). These mental health problems include depression, anxiety, stress, burnout, daytime sleepiness, insomnia, chronic fatigue, and violence (Capasso et al 2018 ; Font et al 2012 ; Sole et al 2013 ).…”
Section: Occupational Health Outcomes For Migrant Workersmentioning
confidence: 99%
“…It is worth noting that in host countries, they can also work in the informal economy. Previous literature has shown that migrant workers are exposed to social vulnerability, and this impacts physical, mental and psychosocial health indicators (Bretones et al., 2020; Ornek et al., 2020), increasing the risk of occupational injuries in the workplace (Arici et al., 2019; Hargreaves et al., 2019; Sterud et al., 2018). These conditions can become worse in specific groups, such as women (Sanchón‐Macias et al., 2016), people with undocumented status (Martinez et al., 2015), and those living in areas with high social deprivation (Kearns et al., 2017).…”
Section: Introductionmentioning
confidence: 99%